Coincidental retinal dysplasia in patients presenting with pseudohypopyon: a series of two cases. Issue 4 (15th April 2020) - Jakati, Saumya; Patel, Anamika; Pathengay, Avinash; Kaliki, Swathi
Abstract : Clinical diagnosis is always challenging in cases with atypical presentation. Herein, we present two cases which masqueraded as ocular infection/inflammation on presentation, were clinically suspicious for retinoblastoma, and histopathology revealed the diagnosis of retinal dysplasia. Case 1 had left corneal perforation with anterior chamber exudates on presentation. On ultrasound B-scan, ill-defined mass was noted, raising a suspicion of malignancy. MRI showed dilated ventricles with midline shift. Vitreous cytology was inconclusive. Enucleation was performed as malignancy could not be ruled out. Histopathology revealed detached retina with dysplastic rosettes in addition to inflammation and multinucleate giant cell reaction. Case 2 presented with right eye anterior chamber pseudohypopyon. Fundus examination revealed diffuse vitreous haze and a suspicious mass in the retinal periphery raising suspicion for retinoblastoma. Histopathology revealed the diagnosis of retinal dysplasia.